Effect of oral anticoagulation on left atrial appendage thrombus resolution in patients with rheumatic mitral stenosis: A prospective observational study. (Student's Journal of Health Research Africa, 2025)
Background:Rheumatic mitral stenosis (MS) remains a major cause of cardiovascular morbidity in developing countries and is frequently complicated by atrial fibrillation and left atrial appendage (LAA) thrombus formation. The presence of LAA thrombus significantly increases thromboembolic risk and contraindicates interventional procedures such as percutaneous transvenous mitral commissurotomy (PTMC). Objectives:To evaluate the effect of oral anticoagulation on the resolution of left atrial appendage thrombus in patients with rheumatic mitral stenosis and to identify clinical and echocardiographic predictors of thrombus clearance. Methods:This prospective hospital-based observational study was conducted in the Department of Cardiology, Indira Gandhi Institute of Medical Sciences, Patna. Thirty patients with severe isolated rheumatic mitral stenosis and documented LAA thrombus on transesophageal echocardiography (TEE) were enrolled. All patients received oral anticoagulation with acenocoumarol and were followed for 12 weeks with weekly INR monitoring, targeting a therapeutic range of 2.0–2.5. Results:Most patients were young adults with a female predominance, and atrial fibrillation was present in 73.3%. Oral anticoagulation led to a significant reduction in mean LAA thrombus size from 5.34 ± 4.42 cm² at baseline to 3.82 ± 4.03 cm² after treatment. A substantial proportion of patients achieved complete thrombus resolution, while others demonstrated partial clearance. Reduction in spontaneous echo contrast intensity was also observed. Thrombus resolution was more likely in patients with smaller baseline thrombus size, sinus rhythm, lower left atrial dimensions, higher LAA emptying velocities, and sustained therapeutic INR levels. Conclusion:Oral anticoagulation with acenocoumarol is effective in achieving complete or partial resolution of left atrial appendage thrombus in patients with rheumatic mitral stenosis. Adequate INR control and favorable echocardiographic parameters play a critical role in thrombus clearance. Recommendation:Structured vitamin K antagonist therapy with strict INR monitoring and repeat transesophageal echocardiography should be routinely employed before considering interventional procedures in this high-risk population.
Keywords: Rheumatic mitral stenosis; Left atrial appendage thrombus; Oral anticoagulation; Transesophageal echocardiography; Acenocoumarol